(untitled) (Journal of Industrial and Mechanical Engineering, 2022)
At the time of succession, family SMEs face various difficulties that in certain cases end with the closure of the company or its sale to third parties. The issue of family SMEs has been widely addressed by the specialized literature from different perspectives, however, it is observed that the analysis of the expectations, motivations and behavior of the new generations of young people who succeed the founders, particularly in the Latin American context, have not been addressed in all its dimensions. Family relationships, as well as the form of communication, the definition of success or the motivational elements in the young people of the so-called "new generations" (millennials, generation X among others) are in constant transformation. For this reason, this work intends, from the bibliometric approach, to analyze and understand these changes and identify how they impact the success or failure of inter-generational transfer in family SMEs.